(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The article is devoted to the study of historical aspects of the development of the science of financial security of joint stock companies in Ukraine. The purpose of the work is to systematize the domestic economic literature on the issues of financial security and to distinguish its main features in the historical aspect. The article also provides an overview of the legislative framework in Ukraine regarding the provision of financial security and identifies the main threats to Ukraine’s financial security. It is proved that financial security is the most important component of the economic and national security of Ukraine as a whole. The author systematizes the evolution of approaches to the definition of «financial security» and proposes to distinguish three main stages of the national science of financial security. The first stage is characterized as the period of the birth of a national science of financial security of the state or enterprise. The second stage is identified as a period of active legislative initiatives on legal regulation of financial security in Ukraine. The third stage is a modern science on financial security of Ukraine. At this stage, the study of the concept of financial security is deepening in two directions: 1) financial security is considered at different levels of the economy and separates the science of financial security of the state, financial security of the region and financial security of individual economic entities; 2) financial security is considered from the point of view of its origins, namely, scientific researches on debt security, currency security, safety of insurance and stock markets, budget security, and bank security appear. The proposed periodization of scientific approaches to the development of the concept of «financial security» allows a deeper interpretation of this concept, determines its necessity for further research categorical apparatus of the concept of financial security of joint stock companies and the identification of typological characteristics of the notion of financial security of corporate structures.